A Companion to the Fairy Tale. - Davidson, Hilda Ellis; Chaudhri, Anna (Boydell & Brewer Ltd., 2003)
Introduction is given by Derek Brewer. The aim of this book is to discuss the characteristics of the traditional fairy tale in Europe and North America, and various theories of its development and interpretation. The book deals with the main collections - the Grimm brothers, Hans Andersen, Perrault and Afanes'ev - and with the development of tales in various regions of Europe, including Ireland, Wales, Scandinavia, Germany and Russia, as well as India, where it was once claimed that they originated. The subject of the fairy tale is a controversial one: problems discussed here include the relationship between tales recorded from story-tellers and literary works, the importance of printed works for the spread of the tales, the growth of recent examples with a feminine approach, the spread of popular tales like "Cinderella", special types like the cumulative tales, possible effects of TV, and the nature of traditional plots and characters. Above all, we have been concerned with the distribution and long survival of these tales, and the nature of their appeal. It is shortlisted for the katharine briggs folklore award 2004.; Contributors are: Graham Anderson, David Blamires, Ruth Bottigheimer, Derek Brewer, Mary Brockington, Anna Chaudhri, Hilda Ellis Davidson, Robin Gwyndaf, Bengt Holbek, David Hunt, Reimund Kvideland, Patricia Lysaght, Neil Philip, James Riordan, Pat Schaefer, Tom Shippey, and Joyce Thomas.